A memória do não desejável : sentidos históricos e ideológicos das imagens do caderno “A cara do racismo no Brasil”, elaborado por professores e professoras do município de Santo Estevão - BA - Smigura, Marcela Souza Macedo (2024)
This research aimed to analyze the images and texts from the textbooks used in remote activities, specifically those from the third edition, whose theme was “The face of racism in Brazil”, from a total of six editions. The textbooks were defined as teaching materials created by teachers from the city of Santo Estevão-BA, and were made with the intention of providing learning in times of face-to-face activities suspension due to the contagion of the COVID-19 virus, in the year 2020, marked by decrees that suspended classes throughout all the territory of Bahia. It is important to highlight that this research is qualitative; and Discourse Analysis was adopted as a methodological subsidy for processing images and texts. In this sense, an analysis was generated based on socio-historical and ideological elements, subject, ideology and discourse, weaving dialogues with Eni Orlandi, Foucault and Pêcheux, treating the different discursive materialities regarding racism and its tentacles, identifying its agents and the disposition of racial discourses. For the analysis of racial discourses, we used a theoretical framework based on black authors, such as Grada Kilomba, Kabenguele Munanga, Nilma Lino Gomes, bell hooks,Franz Fanon, Silvio Almeida and other theorists who helped in the approaches to race, discrimination, prejudice and racism. In the image analysis, we realized that the material constitutes an important research document, serving as a parameter for actions that include anti-racist education. But, on the other hand, the need for work based on Law 10.639/03 and the importance of imagetic literacy for the teachers formation were noticeable due to the use of images supported by theoretical texts. We can conclude that the images selected by the teachers to contemplate the act of teaching about racism are important, as they disseminate positive representations that value the black people and black culture, and have as principle the breaking of stereotypes of black men and women in the brazilian society, constituting themselves as positive aspects for an anti-racist education.